The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1364/optica.6.000128
|View full text |Cite
|
Sign up to set email alerts
|

High-channel-count 20  GHz passively mode-locked quantum dot laser directly grown on Si with 41  Tbit/s transmission capacity

Abstract: Low cost, small footprint, highly efficient and mass producible on-chip wavelength-division-multiplexing (WDM) light sources are key components in future silicon electronic and photonic integrated circuits (EPICs) which can fulfill the rapidly increasing bandwidth and lower energy per bit requirements. We present here, for the first time, a low noise high-channel-count 20 GHz passively mode locked quantum dot laser grown on complementary metaloxide-semiconductor compatible on-axis (001) silicon substrate. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(62 citation statements)
references
References 33 publications
(38 reference statements)
0
60
2
Order By: Relevance
“…Measurements without the use of the booster optical amplifier have shown that neither the −3 dB spectral width nor the timing jitter is influenced by the booster optical amplifier, only the baseline for L(f) at −120 dBc/Hz is increasing due to the lower power impinging onto the detector. The lowest identified value of 9 fs for the pulse-to-pulse timing jitter for this laser is 1.5 times higher than the one for the lowest timing jitter obtained so far by a passively mode-locked quantum dot laser on silicon of 6 fs at 20 GHz with a 1.6 times broader pulse width at this operation point [1] than the device presented in this work. in this area for nonlinear intensity auto-correlation.…”
Section: Mode-locking Pulse Train and Stability Characterizationcontrasting
confidence: 58%
See 3 more Smart Citations
“…Measurements without the use of the booster optical amplifier have shown that neither the −3 dB spectral width nor the timing jitter is influenced by the booster optical amplifier, only the baseline for L(f) at −120 dBc/Hz is increasing due to the lower power impinging onto the detector. The lowest identified value of 9 fs for the pulse-to-pulse timing jitter for this laser is 1.5 times higher than the one for the lowest timing jitter obtained so far by a passively mode-locked quantum dot laser on silicon of 6 fs at 20 GHz with a 1.6 times broader pulse width at this operation point [1] than the device presented in this work. in this area for nonlinear intensity auto-correlation.…”
Section: Mode-locking Pulse Train and Stability Characterizationcontrasting
confidence: 58%
“…In literature, line widths of 100 kHz (−3 dB) for a self mode-locked quantum dot laser on silicon [36] and 80 kHz for a similar device presented here [35] were reported indicating a 200-250 times broader repetition rate line width as compared to the here presented results although no precise pulse train stability analysis in terms of radio-frequency line width has been carried out yet for these devices. Additionally, in the results presented here, a 2.75 times narrower repetition rate line width is observed as compared to the reported repetition rate line width of 1.1 kHz from a complex tapered waveguide design from a silicon quantum-well laser [34] and 4.5 times narrower line width compared to the 1.8 kHz width reported for a monolithic InAs quantum dot passively mode-locked two-section laser on silicon [1]. Comparing the achieved timing stability with quantum dot passively mode-locked lasers on native substrates, except of silicon, repetition rate line widths ranging from 500 Hz up to 27 kHz [37,[39][40][41][42][43] have been reported.…”
Section: Mode-locking Pulse Train and Stability Characterizationcontrasting
confidence: 44%
See 2 more Smart Citations
“…Inhomogeneous broadening effect in self-assembled QD structure effectively broadens the optical gain bandwidth. It can enable widely tunable single-wavelength lasers [3] and large comb width to fit more wavelength channels [15]. But it also can easily support multiple longitudinal mode lasing in lasers without a fine wavelength selection mechanism, such as microring lasers whose lasing mode space is only determined by laser cavity free spectral range (FSR).…”
Section: Spectral Measurementmentioning
confidence: 99%